Histological Characteristics of Submandibular Gland after Induction of Hypothyroidism in Adult Albino Rat - Nida Qasim Hayat,Shahnila Nadir,Muhammad Umar Farooq (Journal of Rawalpindi Medical College, 2016)
Background: To investigate the histological changes in the submandibular salivary gland of the rat after inducing hypothyroidism by methimazole. Methods: The study included twenty male albino rats, weighing between 130-150 grams. They were divided into two groups. Group A (n=10) as the control group and Group B (n=10) was labeled as the experimental group. Group A was given normal feed and water. Whereas, group B was given methimazole (MMI) as 0.02% solution in drinking water daily for 3-weeks. Submandibular glands were excised, weighed and processed for light microscopy on 22nd day. It was fixed in Bouin’s fluid . For histological analysis H&E stain was used. For the confirmation of hypothyroid state of albino rat serum T3, T4 and TSH levels were done by enzyme immunoassay. Results: Statistically significant decrease in the concentrations of T3, T4 and a statistically significant increase in the serum concentration of TSH was observed when the experimental group was compared to the control. Results showed no significant difference in combined weight of submandibular and sublingual salivary glands between group A and B (p=0.397). Histological analysis of submandibular gland was done under light microscope. Group A showed normal morphology. Whereas, Pearson Chi-Square test showed atrophic changes in serous acini of group B . Fishers Exact Test showed the presence of heterochromatic nuclei in the submandibular gland of the same group . Increased connective tissue was also observed in group B . No significant difference was observed in the mean number of vacuoles present in the submandibular gland of the control and the experimental group (p=0.535) .Significant difference was observed in the mean diameter of the striated ducts of the submandibular gland of the control and the experimental (p<0.007) . Conclusion: Histology of the submandibular salivary gland is affected by hypothyroidism resulting in changes in the histological features of the gland.